The Impact Of Expectations On Newcomer Performance In Teams As Mediated By Work Characteristics, Social Exchanges, And Empowerment - Chen, Gilad; Klimoski, Richard J. (Academy of Management Journal, 2003)
Integrating research on the Pygmalion and Galatea effects with a group socialization model and theories of work motivation and interpersonal leadership, we delineated and tested a model of newcomer role performance in work teams. A two-month field study of 70 newcomers, 70 team leaders, and 102 teammates in high-tech project teams supported the model. In particular, newcomer general self-efficacy and experience predicted newcomer and team expectations, and motivational and interpersonal processes (captured by work characteristics, social exchanges, and empowerment) helped link expectations and newcomer role performance.